Brand Identity Produk Owa Outdoor Di Wilayah Malang Raya Sebagai Media Promosi - Rendy Setyawan Putra; Handry Rochmad Dwi Happy (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2021)
The development of dressing while on vacation in the open has been a very trend among teenagers and adults. Owa Outdoor is a brand store that sells clothing such as jackets, flannel shirts, shirts, pants, and bags. With the change of name and logo, what was originally called Owa Store became Owa Outdoor, so there was the introduction of a new identity.The solution offered in this research is the design of the Brand Identity for Outdoor Gibbons as a promotional medium. Where Brand Identity is an element of a brand that can be seen with the naked eye which can be in the form of characters, aspects of color, symbols or typologies that contain the value of a product in a company that is intended so that consumers understand the product.The results of the test using the questionnaire method in this study showed that of the five target consumers who agreed with the Brand Identity design, they were able to introduce, give trust and attract consumers with packaging and merchandising.